Pemanfaatan Kompos Bulu Ayam untuk Budidaya Selada di Lahan Tailing Pasir Bekas Penambangan Timah - Ismed Inonu; R. Kusmiadi; N. Mauliana (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2016)
Inonu, et.al. Use of Composted Chicken Feathers for Lettuce Cultivation in Sand Tailings of ex Tin-Mining Site. JLSO 5(2):145-152.Chicken feathers is a solid waste which can be composted for sand tailings of ex tin-mining site ameliorating. The objective of this research was to analysis the different doses of composted chicken feathers to obtain the proper dosage for growth and production of lettuce grown on sand tailings of ex tin-mining site. This research used experimental method with Randomized Completely Block Design (RCBD). The treatment factor were doses of composted chicken feathers with five levels (5.0; 7.5; 10; 12.5; 15 tons/ha of chicken feathers) and 20 tons/ha of chicken manure as a control. The results showed growth and production of lettuce were treated with 20 tons / ha of chicken manure is higher than all treatment of doses of composted chicken feathers. Sand tailings of ex tin-mining site which is treated 12.55 tons/ha composted chicken feathers produced the highest growth and production of lettuce.